2019
DOI: 10.33485/jiik-wk.v5i2.133
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Terjadinya Anemia Pada Ibu Hamil Trimester Ii

Abstract: The World Health Organization (WHO) in 2015 is estimated as many as 52.5% of pregnant women in Southeast Asia who experience anemia. 3,4 in various countries, including Indonesia, reported that the incidence of anemia is still high. To prove determine the affecting factors to the occurrence of anemia in trimester II pregnant women at Kutalimbaru Health Center, Deli Serdang District in 2018. Tyfe of research design was an analytical survey with a cross sectional approach. The population of this study was trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
4
1
5
Order By: Relevance
“…Local people still believe in myths related to dietary restrictions in pregnant women so that the nutrients obtained by pregnant women are still lacking. This is in accordance with research conducted at the Kutalimbaru PHC in Deli Serdang in 2018 which stated that pregnant women who had poor nutrition increased the risk of experiencing anemia [42]. Moreover, a study conducted at the Rekas PHC in 2017 suggested that the husband's knowledge and support also play a role in non-infectious health disorders of pregnant women [43].…”
Section: Chronic Energy Deficiency In Pregnancysupporting
confidence: 85%
“…Local people still believe in myths related to dietary restrictions in pregnant women so that the nutrients obtained by pregnant women are still lacking. This is in accordance with research conducted at the Kutalimbaru PHC in Deli Serdang in 2018 which stated that pregnant women who had poor nutrition increased the risk of experiencing anemia [42]. Moreover, a study conducted at the Rekas PHC in 2017 suggested that the husband's knowledge and support also play a role in non-infectious health disorders of pregnant women [43].…”
Section: Chronic Energy Deficiency In Pregnancysupporting
confidence: 85%
“…Taksiran berat janin dianggap penting pada masa kehamilan karena pertumbuhan janin intra uterin berlangsung tidak konstan dan berhubungan dengan resiko terjadinya komplikasi selama persalinan pada ibu dan bayi seperti lahir rendah atau berat lahir berlebih (Lamdayani & Olivia, 2019). Distribusi frekuensi pengetahuan responden dikelompokkan menjadi 3 yaitu kurang,cukup dan baik.…”
Section: Pembahasan Pengetahuan Dan Tbjunclassified
“…Hasil ini sejalan dengan penelitian Aisyah (2018) bahwa ada hubungan sikap selama hamil dengan berat badan bayi baru lahir di klinik Niar Amplas Medan tahun 2018. Selain itu, Lamdayani & Olivia (2019) juga menemukan bahwa ada hubungan antara peningkatan berat badan dengan estimasi berat badan janin. Menurut Mariana et al, (2018) sebagian besar responden ibu hamil mempunyai pola makan yang tidak sehat dan sebagian kecilnya lagi mengalami anemia.…”
Section: Sikap Dan Tbjunclassified
“…Berdasarkan hasil literature review ibu hamil dengan anemia terhadap 5 artikel yaitu Wahtini dan Evi (2020) [7], Gedefaw et al (2015) [8], Putri et al (2015) [9], Damanik (2019) [10]dan Yanti et al (2015) [11].…”
Section: Hasil Dan Pembahasan Hasilunclassified